Salt sensitivity potentiates high-salt diet-induced intestinal barrier disruption and gut microbiome dysbiosis in rats - Zeng, Baihan; Peng, Xile; Xiao, Pengyang; Nie, Kaidi; Zhang, Guilong; Xia, Lina (Frontiers in Microbiology, 2026)
IntroductionThe high-salt diet is a prevalent eating habit associated with health risks. This study investigated the impact of high salt on intestinal barrier disruption and gut microbiome dysbiosis using Wistar and Dahl salt-sensitive rat models.MethodsRats were fed a normal diet or a high-salt diet for eight weeks. Body weight and plasma inflammatory cytokines were monitored in the study. Colon tissue damage was assessed via histopathological examination, and metagenomic sequencing was utilized to analyze alterations in microbial composition, functional pathways, and biodiversity.ResultsThe results indicated that high salt significantly elevated pro-inflammatory cytokine levels and induced structural damage in the colon. Metagenomic analysis revealed that high salt concentrations resulted in approximately a 15% difference in microbial species composition. And led to a decrease in Alpha diversity, along with an increase in the Firmicutes/Bacteroidetes ratio. Taxon-specific alterations included reduced abundance of Lactobacillus and Clostridium, and increased abundance of Enterobacter and Bifidobacterium. Correlation analyses further revealed a positive correlation between Bifidobacterium abundance and tumor necrosis factor-α level in Dahl salt-sensitive rats.DiscussionThis study illuminates the gut microbiota’s role in salt-sensitivity and provides a foundational basis for developing microbiota-targeted interventions for at-risk individuals.